Co-delivery of siRNAs and anti-cancer drugs using layered double hydroxide nanoparticles - Li, Li; Gu, Wenyi; Chen, Jiezhong; Chen, Weiyu; Xu, Zhi P. (Biomaterials, 2014)
In this research we employed layered double hydroxide nanoparticles (LDHs) to simultaneously deliver an anticancer drug 5-fluorouracil (5-FU) and Allstars Cell Death siRNA (CD-siRNA) for effective cancer treatment. The strategy takes advantage of the LDH anion exchange capacity to intercalate 5-FU into its interlayer spacing and load siRNA on the surface of LDH nanoparticles. LDH nanoparticles have been previously demonstrated as an effective cellular delivery system for 5-FU and siRNA separately in various investigations. More excitedly, the combination of CD-siRNA and anticancer drug 5-FU with the same LDH particles significantly enhanced cytotoxicity to three cancer cell lines, e.g. MCF-7, U2OS and HCT-116, compared to the single treatment with either CD-siRNA or 5-FU. This enhancement is probably a result of coordinate mitochondrial damage process. Thus, the strategy to co-deliver siRNA and an anticancer drug by LDHs has great potential to overcome the drug resistance and enhance cancer treatment.